Peran Sosialisasi Hukum dalam Pencegahan Perilaku Bullying : Kajian Hukum Pidana dan Perlindungan Anak di Desa Sumeith Pasinaro - Cut Charolina Pattiwaellapia; Ronald Darlly Hukubun; Riskia Tirta Nirwana Sopacua; Jehuda Daniel Nussy; Rocky Genestho Kubela; Deirdre Livia Petta; Vanessa Yosiana Matital; Abdul Mahid Ukratalo (Pusat Riset dan Inovasi Nasional, 2026)
Bullying in Indonesian educational settings remains a serious problem that requires widespread attention. Poor legal understanding among children and adolescents, coupled with suboptimal child protection regulations, increases the risk of violence in schools. To address this issue, a